Clinical use of iterative 4D-cone beam computed tomography reconstructions to investigate respiratory tumor motion in lung cancer patients. (August 2014) - Schmidt, Mai L.; Poulsen, Per R.; Toftegaard, Jakob; Hoffmann, Lone; Hansen, David; Sørensen, Thomas S.
Abstract Background. Cone beam computed tomography (CBCT) provides means for respiratory resolved volumetric imaging of the thorax. However, merely sorting the acquired projections into respiratory phases and performing a series of conventional three-dimensional (3D) reconstructions lead to clinically prohibitive reconstruction artifacts. This problem can be mitigated by iterative 4D reconstruction. We present a clinical evaluation of two iterative 4D-CBCT reconstruction algorithms during stereotactic body radiation therapy. Material and methods. Two types of iterative 4D-CBCT reconstructions were performed utilizing: 1) total variation (TV) minimization; and 2) optical flow (OF) based deformable registration between phases. The reconstructions were initially evaluated on a lung phantom with a moveable target insert. Subsequently, 4D-CBCT reconstructions were performed for 19 patients on 2–3 CBCT projection datasets previously acquired for conventional 3D-CBCT reconstruction (∼650 half-fan projections per scan in a full one-minute gantry rotation). The 4D reconstructions were imported into a treatment planning system, where the gross tumor volume (GTV) was delineated and used to extract the tumor motion amplitude. Results. For both phantom and patient scans, the iterative 4D-CBCT reconstructions had sufficient quality for GTV delineation when the breathing period was faster than 3.5 seconds (15 of 19 patients), but not for slower breathing periods (4 patients). The 3D tumor motion amplitude for the patients was significantly lower (p = 10−6, Wilcoxon signed rank test) in the OF reconstructions (mean 4.0 mm) than in the TV reconstructions (mean 5.3 mm). Conclusion. TV and OF iterative 4D-CBCT reconstruction of the thorax in a lung phantom and for 19 patients was demonstrated from standard CBCT scans and used to estimate the daily lung tumor motion.